2009
DOI: 10.1091/mbc.e08-07-0745
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in theArabidopsisPeroxisomal ABC Transporter COMATOSE Allow Differentiation between Multiple Functions In Planta: Insights from an Allelic Series

Abstract: COMATOSE (CTS), the Arabidopsis homologue of human Adrenoleukodystrophy protein (ALDP), is required for import of substrates for peroxisomal ␤-oxidation.A new allelic series and a homology model based on the bacterial ABC transporter, Sav1866, provide novel insights into structure-function relations of ABC subfamily D proteins. In contrast to ALDP, where the majority of mutations result in protein absence from the peroxisomal membrane, all CTS mutants produced stable protein. Mutation of conserved residues in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 86 publications
(159 reference statements)
6
60
0
1
Order By: Relevance
“…The K487A mutant was generated by site-directed mutagenesis, as described in Dietrich et al (28). To create an in-frame CFP fusion with a 10-amino acid spacer between the C terminus of CTS and CFP, the native stop codon of CTS was removed by site-directed mutagenesis using the QuikChange II site-directed mutagenesis kit (Stratagene, La Jolla, CA), with primer pair CTSstopF (GAACAGACAACAG-AGTCAGAATTCGATATCAAGC) and CTSstopR (CTTGT-CTGTTGTCTCAGTCTTAAGCTATAGTTCG), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The K487A mutant was generated by site-directed mutagenesis, as described in Dietrich et al (28). To create an in-frame CFP fusion with a 10-amino acid spacer between the C terminus of CTS and CFP, the native stop codon of CTS was removed by site-directed mutagenesis using the QuikChange II site-directed mutagenesis kit (Stratagene, La Jolla, CA), with primer pair CTSstopF (GAACAGACAACAG-AGTCAGAATTCGATATCAAGC) and CTSstopR (CTTGT-CTGTTGTCTCAGTCTTAAGCTATAGTTCG), according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of cts null mutants has demonstrated that CTS plays key roles in a number of developmental and physiological processes, including germination, seedling establishment, fertility, root growth, and dark-induced senescence (16 -18, 20 -27). The different roles of CTS in planta are separable by mutagenesis (28) and can be related to different biochemical roles, specifically the ability to metabolize distinct substrates such as fatty acids and hormone precursors via ␤-oxidation. Taken together, these findings strongly suggest that CTS is a transporter with broad acyl chain specificity, which mediates uptake of substrates for ␤-oxidation into the peroxisome.…”
mentioning
confidence: 99%
“…Nile red stains positively for lipids in plants Pighin et al, 2004;Schmidt and Herman, 2008;Dietrich et al, 2009), fluorescing red in the presence of polar lipids and yellow when staining esterified cholesterol and triacylglycerols (Diaz et al, 2008). This approach showed polar lipids in the PBS of maize, but in the oat parental line, only the MS and some of the veinal cells stained (Fig.…”
Section: Maize Chromosome 3 Introduction Causes Lipid Deposition In Omentioning
confidence: 92%
“…These data suggest that the two nucleotide binding domains are functionally distinct and that the substrate selectivity can be altered [11]. Lousa et al (O34) also showed that CTS forms a high molecular weight complex suggesting that the protein might interact with other components involved in fatty acid catabolism.…”
Section: Eastmond Et Al (O33)mentioning
confidence: 93%
“…This protein is a homologue of human ALDP, which has been implicated in the disease X-linked Adrenoleukodystrophy [11]. It is probable that CTS imports either free fatty acids or acyl-CoAs into the peroxisome, but its precise substrate specificity is not known.…”
Section: Eastmond Et Al (O33)mentioning
confidence: 99%